Humans (really) are animals: picture-book reading influences 5-year-old urban children’s construal of the relation between humans and non-human animals - Waxman, Sandra R.; Herrmann, Patricia; Woodring, Jennifer; Medin, Douglas (Frontiers in Psychology, 2014)
What is the relation between humans and non-human animals? From a biological perspective, we view humans as one species among many, but in the fables and films we create for children, we often offer an anthropocentric perspective, imbuing non-human animals with human-like characteristics. What are the consequences of these distinctly different perspectives on children’s reasoning about the natural world? Some have argued that children universally begin with an anthropocentric perspective and that acquiring a biological perspective requires a basic conceptual change (cf. Carey, 1985). But recent work reveals that this anthropocentric perspective, evidenced in urban 5-year-olds, is not evident in 3-year-olds (Herrmann etal., 2010). This indicates that the anthropocentric perspective is not an obligatory first step in children’s reasoning about biological phenomena. In the current paper, we introduced a priming manipulation to assess whether 5-year-olds’ reasoning about a novel biological property is influenced by the perspectives they encounter in children’s books. Just before participating in a reasoning task, each child read a book about bears with an experimenter. What varied was whether bears were depicted from an anthropomorphic (Berenstain Bears) or biological perspective (Animal Encyclopedia). The priming had a dramatic effect. Children reading the Berenstain Bears showed the standard anthropocentric reasoning pattern, but those reading the Animal Encyclopedia adopted a biological pattern. This offers evidence that urban 5-year-olds can adopt either a biological or a human-centered stance, depending upon the context. Thus, children’s books and other media are double-edged swords. Media may (inadvertently) support human-centered reasoning in young children, but may also be instrumental in redirecting children’s attention to a biological model.